ASHP National Survey of Pharmacy Practice in Hospital Settings: Clinical services and workforce—2021. - Schneider, Philip J; Pedersen, Craig A; Ganio, Michael C; Scheckelhoff, Douglas J (American Journal of Health-System Pharmacy, 2022)
Purpose Results of the 2021 ASHP National Survey of Pharmacy Practice in Hospital Settings are presented. Methods Pharmacy directors at 1,498 general and children's medical/surgical hospitals in the United States were surveyed using a mixed-mode method of contact by email and mail. Survey completion was online. IQVIA supplied data on hospital characteristics; the survey sample was drawn from IQVIA's hospital database. Results The response rate was 21.9%. Pharmacists are routinely assigned to a majority of patients at least 8 hours per day, 5 days per week in 70.4% of hospitals. This is an increase from 60.8% in 2018 and has steadily increased over the past decade. Pharmacists independently prescribe medications pursuant to a diagnosis in 30.9% of hospitals, an increase from 21.1% in 2020. Pharmacists have prescribing authority in 67% of health-system ambulatory clinics and can recommend or schedule pharmacogenomics testing for drug and dosage selection in 11.4% of hospitals, an increase from 5.4% in 2019. Pharmacists are using electronic methods in 82.5% of hospitals to collect information for monitoring medication therapy. Shortages of entry-level pharmacy technicians are acute, with 73.4% of survey respondents reporting a shortage. Technician shortages have affected pharmacy operations and have prompted new recruitment and retention strategies. Conclusion Despite workforce challenges, clinical pharmacy services continue to expand to cover increasing numbers of patients with medication management services in both the inpatient and outpatient settings. The use of data analytics and pharmacy technicians has contributed to this evolution. Addressing the workforce challenges will be critical to sustain this progress.